Projection of intra-urban modification of night-time climate indices during the 21st century - Skarbit, Nóra; Gál, Tamás (Hungarian Geographical Bulletin, 2016)
The present paper evaluates the alteration of certain night-time climate indices namely warm nights (Tmin ≧ 17 °C) and tropical nights (Tmin ≧ 20 °C) during the 21st century in the city of Szeged. This examination was performed within the framework of a project founded by International Visegrad Fund, where the change of more climate indices were examined in several Central European cities. In this study the MUKLIMO_3 microclimatic model was used, which ensured the modelling of the local scale processes in the examined area. In the model for the land use we applied the Local Climate Zone (LCZ) system. In order to analyze longer periods the cuboid method was applied, which is a dynamical-statistical downscaling technique. We calculated the indices for 1981-2010 based on measurements and for 2021-2050 and 2071-2100 from the EURO-CORDEX datasets. In this study we present the results of Representative Concentration Pathways (RCP) scenarios namely RCP 4.5 and RCP 8.5. Our results show that highest values appear in the city centre and the number of the days clearly increases in the 21st century especially according to scenario RCP 8.5. The values depend on the built-up types and there are more days towards to the densely built-up LCZs. Moreover, considering the relative changes of the zones, larger values appear in sparsely built-up zones and natural surfaces.